Obesity and Impaired Metabolic Health Increase Risk of COVID-19-Related Mortality in Young and Middle-Aged Adults to the Level Observed in Older People: The LEOSS Registry - Stefan, Norbert; Sippel, Katrin; Heni, Martin; Fritsche, Andreas; Wagner, Robert; Jakob, Carolin E. M.; Preißl, Hubert; von Werder, Alexander; Khodamoradi, Yascha; Borgmann, Stefan; Rüthrich, Maria Madeleine; Hanses, Frank; et al. (Frontiers in Medicine, 2022)
Advanced age, followed by male sex, by far poses the greatest risk for severe COVID-19. An unresolved question is the extent to which modifiable comorbidities increase the risk of COVID-19-related mortality among younger patients, in whom COVID-19-related hospitalization strongly increased in 2021. A total of 3163 patients with SARS-COV-2 diagnosis in the Lean European Open Survey on SARS-CoV-2-Infected Patients (LEOSS) cohort were studied. LEOSS is a European non-interventional multi-center cohort study established in March 2020 to investigate the epidemiology and clinical course of SARS-CoV-2 infection. Data from hospitalized patients and those who received ambulatory care, with a positive SARS-CoV-2 test, were included in the study. An additive effect of obesity, diabetes and hypertension on the risk of mortality was observed, which was particularly strong in young and middle-aged patients. Compared to young and middle-aged (18-55 years) patients without obesity, diabetes and hypertension (non-obese and metabolically healthy; n=593), young and middle-aged adult patients with all three risk parameters (obese and metabolically unhealthy; n=31) had a similar adjusted increased risk of mortality (OR 7.42 [95% CI 1.55-27.3]) as older (56-75 years) non-obese and metabolically healthy patients (n=339; OR 8.21 [95% CI 4.10-18.3]). Furthermore, increased CRP levels explained part of the elevated risk of COVID-19-related mortality with age, specifically in the absence of obesity and impaired metabolic health. In conclusion, the modifiable risk factors obesity, diabetes and hypertension increase the risk of COVID-19-related mortality in young and middle-aged patients to the level of risk observed in advanced age.